2015
DOI: 10.5588/ijtld.15.0418
|View full text |Cite
|
Sign up to set email alerts
|

Childhood tuberculosis in the United States: shifting the focus to prevention

Abstract: In the last century, the United States has transitioned from a high to a low tuberculosis (TB) incidence country. A major factor in this decline has been the emphasis on identification and treatment of patients with tuberculous infection. While identification, testing, and preventive therapy pose challenges, recent developments in childhood TB offer more options for effective strategies that are acceptable to both children and their families. These include screening and testing in non-traditional settings, use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In attempts to improve completion rates, some experts have increasingly used the 4-month regimen of rifampin, which had typically been recommended for LTBI treatment among those exposed to isoniazid-resistant strains. 104,105 …”
Section: Managementmentioning
confidence: 99%
“…In attempts to improve completion rates, some experts have increasingly used the 4-month regimen of rifampin, which had typically been recommended for LTBI treatment among those exposed to isoniazid-resistant strains. 104,105 …”
Section: Managementmentioning
confidence: 99%
“…12 Research has already demonstrated that the ingestible sensor has no risk of mechanical injury or toxicology concern. 7,11,13 The ingestible sensor technology has been used in monitoring different diseases such as diabetes, 14 hypertension, 15 mental health disorder, 16 and tuberculosis 13,17 as well as care for kidney transplant patients, 11,13,[17][18][19][20] and has been wellaccepted. 21,22 To use the ingestible sensor to monitor medication taking and measure adherence, the medication must be coencapsulated with the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Young children (aged <5 years) exposed to Mycobacterium tuberculosis ( Mtb ) are at the highest risk of disseminated disease [ 1 ]. The number of tuberculosis cases in children varies between 3.5% and 11% of the total reported global tuberculosis cases, and an estimated 332 000 children are left undiagnosed or not reported in national surveys [ 2 , 3 ].…”
mentioning
confidence: 99%